2007
DOI: 10.1111/j.1526-4610.2007.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Topiramate on Health‐Related Quality of Life Indicators in Chronic Migraine

Abstract: Compared with placebo-treated patients, topiramate 100 mg/day appears to contribute to reductions in migraine-related limitations on daily activities and emotional distress beginning as early as week 4 and continuing up to week 16 after treatment. Physician's Global Impression of Change results are very similar with Subject's Global Impression of Change, indicating concordance between the physician's and the subject's assessment of improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 26 publications
(65 reference statements)
2
46
0
3
Order By: Relevance
“…There may also be reduced quality of life between attacks related to more general feelings of anxiety, depression, irritability, and sleepiness, which have been observed with greater frequency among migraineurs than corresponding population controls [24][25][26][27] However, the degree to which one or more of these health effects are the result of migraine itself, side effects of medication use (e.g., sleepiness), or independent conditions resulting from some shared risk factor for migraine is not fully understood. Randomized, double-blind, placebo-controlled clinical trials of prophylactic migraine treatments exhibiting efficacy in reducing headache days have produce mixed results, with several studies showing a statistically significant benefit on some quality of life indices [28][29][30][31][32] and others failing to do so [33,34]. However, it is not clear from these studies whether reported quality of life gains derived from patients in the active treatment arms feeling better on days in which they otherwise would have suffered migraine or improved quality of life in general during the between attack period.…”
Section: Discussionmentioning
confidence: 99%
“…There may also be reduced quality of life between attacks related to more general feelings of anxiety, depression, irritability, and sleepiness, which have been observed with greater frequency among migraineurs than corresponding population controls [24][25][26][27] However, the degree to which one or more of these health effects are the result of migraine itself, side effects of medication use (e.g., sleepiness), or independent conditions resulting from some shared risk factor for migraine is not fully understood. Randomized, double-blind, placebo-controlled clinical trials of prophylactic migraine treatments exhibiting efficacy in reducing headache days have produce mixed results, with several studies showing a statistically significant benefit on some quality of life indices [28][29][30][31][32] and others failing to do so [33,34]. However, it is not clear from these studies whether reported quality of life gains derived from patients in the active treatment arms feeling better on days in which they otherwise would have suffered migraine or improved quality of life in general during the between attack period.…”
Section: Discussionmentioning
confidence: 99%
“…Health-related quality of life was measured by change from baseline in mean MSQv2.1 score across three domains: role function restrictive (RF), role function preventive (RP), and emotional functioning (EF). MIDs for all domains of the MSQv2.1 have also been established for between-group differences (3.2, 4.6, and 7.5 for RR, RP, and EF, respectively) and within-group changes (+10.9, +8.3, and +12.2 for RR, RP, and EF, respectively) 21,22.…”
Section: Methodsmentioning
confidence: 99%
“…Topiramate is efficacious across a broad range of migraine frequencies [40][41][42] and has been associated with improvements in the performance of daily activities and QOL in episodic [43][44][45] and chronic migraine, as assessed by the MSQ. [46] The most common adverse effects associated with topiramate treatment include paraesthesia, fatigue, appetite loss and difficulty concentrating. [47] Two divalproex sodium formulations (delayed and extended release) are also effective in migraine prophylaxis.…”
Section: The Role Of Migraine Preventionmentioning
confidence: 99%